BTLA Expression and Function Are Impaired on SLE B Cells - Wiedemann, Annika; Lettau, Marie; Weißenberg, Sarah Y.; Stefanski, Ana-Luisa; Schrezenmeier, Eva-Vanessa; Rincon-Arevalo, Hector; Reiter, Karin; Alexander, Tobias; Hiepe, Falk; Lino, Andreia C.; Dörner, Thomas (Frontiers in Immunology, 2021)
B- and T-lymphocyte attenuator (BTLA/CD272) is an inhibitory checkpoint molecule expressed on T and B cells. Prior studies reported defective function of BTLA by T cells in patients with systemic lupus erythematosus (SLE), whereas nothing is known about its role on B cells in SLE, a disease with various B cell abnormalities. Peripheral blood mononuclear cells (PBMCs) from 23 healthy donors (HD) and 34 SLE patients were stained for BTLA and its expression on B cells was assessed. PBMCs or CD27-IgD+ naive B cells were stimulated together with an activating anti-BTLA antibody or an inhibitor of spleen tyrosine kinase (SYK) and differentiation as well as the expression of activation markers CD71, PD-1 and CD86 were analyzed. Our phenotypic and functional studies revealed reduced BTLA expression on CD27-IgD+ naïve B cells from SLE patients (p=0.0017) related to anti-dsDNA antibody titers (p=0.0394) and SIGLEC-1/CD169 expression on monocytes (p=0.0196), a type I interferon marker related to disease activity. BTLA engagement was found to control CpG/TLR9 activation limiting plasmablast (p=0.0156) and B cell memory induction (p=0.0078) in normal B cells in contrast to other B cell activation pathways (CD40, BCR). These BTLA functions were impaired in SLE B cells. Inhibition of SYK was found to mimic the effects of BTLA activity in vitro. Thus, is it possible that reduced BTLA expression and function of CD27-IgD+ antigen- and T cell-inexperienced SLE B cells could be overcome by SYK inhibition which should be tested in future studies as potential therapeutic principle.